Direct and Latent Effects of Pathogen Exposure Across Native and Invasive Amphibian Life Stages - Urbina, Jenny; Bredeweg, Evan M.; Blaustein, Andrew R.; Garcia, Tiffany S. (Frontiers in Veterinary Science, 2021)
Emerging infectious diseases are one of the multiple factors contributing to the current “biodiversity crisis”. As part of the worldwide biodiversity crisis, amphibian populations are declining globally. Chytridiomycosis, an emerging infectious disease, caused by the fungal pathogen Batrachochytrium dendrobatidis (Bd) is a major cause of amphibian population declines. This fungus primarily affects keratinized structures in larval, juvenile, and adult amphibians as well as heart function. However, we know little about how Bd can impact embryos as well as potential latent effects of Bd exposure over ontogeny. Using two different Bd strains and multiple exposure times, we examined the effects of Bd exposure in Pacific chorus frog (Pseudacris regilla), Western toad (Anaxyrus boreas) and American bullfrog (Lithobates catesbeianus) life stages. Using a factorial experimental design, embryos of these three species were exposed to Bd at early and late embryonic stages, with some individuals re-exposed after hatching. Embryonic Bd exposure resulted in differential survival as a function of host species, Bd strain and timing of exposure. P. regilla experienced embryonic mortality when exposed during later developmental stages to one Bd strain. There were no differences across the treatments in embryonic mortality of A. boreas and embryonic mortality of L. catesbeianus occurred in all Bd exposure treatments. We detected latent effects in A. boreas and L. catesbeianus larvae, as mortality increased when individuals had been exposed to any of the Bd strains during the embryonic stage. We also detected direct effects on larval mortality in all three anuran species as a function of Bd strain, and when individuals were double exposed (late in the embryonic stage and again as larvae). Our results suggest that exposure to Bd can directly affect embryo survival and has direct and latent effects on larvae survival of both native and invasive species. However, these impacts were highly context dependent, with timing of exposure and Bd strain influencing the severity of the effects.